“A Model of Christ”: Melito’s Re-Vision of Jewish Akedah Exegeses - De Andrado, Paba Nidhani (Studies in Christian-Jewish Relations, 2017)
Several scholars have proposed that Melito, the second-century bishop of Sardis, manifests awareness of Jewish exegeses of Genesis 22 (or Akedah). This article investigates the extent and implications of Melito’s engagement with that Akedah tradition. The first part of this essay examines the Jewish exegetical strands that were in existence during Melito’s period. The second part analyzes Melito’s Fragments 9, 10 and 11, with reference to the Jewish exegeses. This article demonstrates the depth of Melito’s reliance on and response to the Akedah tradition, as he employs its motifs on Isaac, the ram and the Temple site. The Akedah tradition serves as a stimulus for Melito’s soteriological ideas, as he develops his perspectives on the sacrifice of Christ. The Fragments further reveal Melito’s complex attitude towards Judaism, marked by contact, tension and creativity.